What freedom for what republics? Universal basic income in the 21st century (Indo)Latin America (Revista Rupturas, 2025)
This article proposes to consider basic income not as a matter of social protection, but as the foundation of the exercise of freedom. In this sense, it attempts to develop, from a political philosophy perspective, the theoretical foundations of the importance of creating the material and cultural conditions for the full exercise of freedom, and to give social and political viability to the democracies of the 21st century with the aim of enabling a new social pact of well-being. In this way, a concept that appears more and more frequently in political and social discourses and that is directly linked to the fate of millions of people in Latin America and around the world would be given greater density.
Keywords: real freedom; basic income; autonomy; basic equality; well-being